Validation of diagnostic tests and epidemiology of Helicobacter pylori infection in Bangladesh - Hafeza Aftab; Yoshio Yamaoka; Faruque Ahmed; Azad AK Khan; Phawinee Subsomwong; Muhammad Miftahussurur; Tomohisa Uchida; Hoda M Malaty (Journal of Infection in Developing Countries)
Introduction: Helicobacter pylori infection is associated with gastritis, peptic ulcer, and gastric cancer. We conducted a cross-sectional study to compare five diagnostic tests for H. pylori infection and studied the epidemiology of the infection in Bangladesh.